Environmentally Friendly Approach to Pectin Extraction from Grapefruit Peel: Microwave-Assisted High-Pressure CO2/H2O - Tuğba Öztürk; Hatice Neval Özbek; Derya Koçak Yanık (Foods, 2024)
In this research, pectin extraction from grapefruit peel (GPP) was performed using a microwave-assisted high-pressure CO2/H2O (MW-HPCO2) system. The Box–Behnken design of response surface methodology was applied for the optimization of MW-HPCO2 extraction conditions to obtain the highest pectin yield. The effects of temperature, time, and liquid/solid ratio on pectin yield were examined in the range of 100–150 °C, 5–15 min, and 10–20 mL g−1, respectively. Under the optimum extraction conditions (147 °C, 3 min, and 10 mL g−1), pectin was obtained with a yield of 27.53%. The results obtained showed that the extraction temperature and time had a strong effect on the pectin yield, while the effect of the liquid/solid ratio was not significant, and the pectin was effectively extracted from grapefruit peel (GP) using MW-HPCO2. Additionally, the application of GPP in apricot jam showed that MW-HPCO2-GPP can be used as a thickener in the food industry. The yield and physicochemical properties (ash, protein, galacturonic acid, reducing sugar and methoxyl content, degree of esterification, equivalent weight, color, viscosity) of pectin extracted in the optimum conditions of the MW-HPCO2 method were superior to pectin extracted by the traditional method. The results of this study revealed that MW-HPCO2 could be an innovative green and rapid technique for pectin extraction.